Transorbital stab wound: a case report - Erşahin, Yusuf; Mutluer, Saffet; Güzelbağ, Elif (The Turkish Journal of Pediatrics, 1994)
Stab wounds of the skull are uncommon. They are usually accidental in children. An apparently trivial wound may cause death due to vascular damage or infection. A 5-year-old boy presented with a nail in the left intraorbital region. He fell with a nail in his hand five hours prior to hospital admission. Computed tomographic scans displayed the nail penetrating the cranium through the left orbital roof and extending towards the left anterior clinoid process. The nail was removed under general anesthesia in the operating room. Meningitis developed two days after the removal of the penetrating object and responded well to antibiotics. The pertinent literature was reviewed.